Internatos adventistas no Brasil em questão: os discursos de permanência da filosofia e das práticas educacionais e os indicativos de ocorrência de atualização na condição pós-moderna - Santos, Eduardo Cavalcante de Oliveira (2016)
Adventist colleges in boarding schools were created in Brazil, similar to the US model, in order to prepare "missionaries" to fulfill the "mission" of the Adventist Church Day, depriving students of the living "world "and offering them education and religious training associated with work in the field. A century has passed after the creation of the first Adventist boarding school in Brazil (1915-2015). The world and society have changed and the concept of education has also changed. But the regime of Adventist boarding schools and educational philosophy remained unchanged. This thesis presents a vast literature which provides a rich and detailed look at the history of the foundation of the pioneers boarding schools in Brazil, and on their educational philosophy and practice. In view of the growth in Adventist boarding schools in Brazil and identified actions, we realize that the leadership of the Seventh-day Adventist Church in Brazil is convinced that the maintenance of boarding schools is essential to meet the basic requirements of their educational philosophy, and is not willing to give up certain principles that judges are fundamental to fulfilling its educational mission. However, due to the demands imposed by social and educational changes in the postmodern condition, that same leadership realize that we live in a completely different world from where the foundations of Adventist Educational Philosophy were established, and therefore begins to allow and even promote some upgrades in the form of conducting the Brazilian Adventist boarding schools, approaching so with the reality that surrounds it